Synergetics Of Mass Media Culture And Trends Of Postmodernism In The Modern Information Space Of Russia - SVETLANA, R. (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT This article examines the issue of the synergy of mass media culture and the trends of postmodernism in the modern information space of Russia and provides a complete and sequential analysis of the state of knowledge and importance of this issue. During the work were formulated forecasts (taking into account the plus factors and minus factors) on the nearest state and development of the mass media culture of Russia. RESUMEN Este artículo examina el tema de la sinergia de la cultura de los medios de comunicación y las tendencias de la posmodernidad en el espacio moderno de información de Rusia y proporciona un análisis completo y secuencial del estado del conocimiento y la importancia de este tema. Durante el trabajo se formularon pronósticos (teniendo en cuenta los factores positivos y negativos) sobre el estado más cercano y el desarrollo de la cultura de los medios de comunicación de Rusia.